ANALISIS HUBUNGAN LITERASI DIGITAL DAN LITERASI EKONOMI DENGAN KEBERLANGSUNGAN USAHA MIKRO DAN KECIL DI KOTA MALANG SELAMA MASA PANDEMI COVID-19 - Reynara, Ignatius; Pangestuty, Farah Wulandari (Journal of Development Economic and Social Studies, 2023)
The objective of this research is to identify the relationship between digital and economic literacy and the sustainability of micro and small businesses in Malang City during the Covid-19 pandemic. This quantitative research uses primary data obtained from questionnaires and Spearman’s rank correlation for the data processing. Statistical descriptive method was also used to explain the data’s condition. This study finds that both digital and economic literacies have strong relationships with the sustainability of micro and small businesses in Malang City during the pandemic. Based on the findings, this research discovers a new capital, that is the knowledge capital, for micro and small entrepreneurs who are willing to maintain the sustainability of their business during the pandemic. They need to improve their digital and economic literacy in the operation and promotion of their business in order to maintain and develop their business.